Species Diversity and Abundance of Marine Crabs (Portunidae: Decapoda) from a Collapsible Crab Trap Fishery at Kung Krabaen Bay, Chanthaburi Province, Thailand - Chutapa Kunsook; Pongchai Dumrongrojwatthana (Tropical Life Sciences Research, 2017)
The diversity and abundance of marine crabs from a collapsible crab trap fishery at Kung Krabaen Bay, Gulf of Thailand, were observed from August 2012 to June 2013 using 10 sampling stations. The results showed that there were seven families, 11 genera and 17 species (two anomuran and 15 brachyuran crabs). The two anomuran species were Clibanarius virescens (1,710 individuals) and Clibanarius infraspinatus (558 individuals). For brachyuran crabs, Portunidae was the most common family, including 10 species. The dominant species of brachyuran crabs included Thalamita crenata (897 individuals), Portunus pelagicus (806 individuals), Charybdis affinis (344 individuals), Scylla sp. (201 individuals), and Charybdis anisodon (100 individuals). The abundance of crabs was affected by the habitat type. Anomuran crabs had the highest abundance in Halodule pinifolia seagrass beds, whilst brachyurans had the highest abundance in Enhalus acoroides seagrass beds. The dominant brachyuran species were found in pelagic areas near the bay mouth, such as P. pelagicus, P. sanguinolentus, C. feriatus, C. helleri, C. natator, C. affinis, and M. hardwickii. Lastly, reforested mangroves were important habitats for Scylla tranquebarica and C. anisodon. Seasonal and physical factors influenced the abundance of some crabs, for example, the abundance of C. virescens was correlated with temperature, and the abundance of T. crenata was correlated with transparency depth. Our results revealed that Kung Krabaen Bay serves as the home to many marine crab species; however, our results also revealed that 49% of the harvested crabs (2,308 out of 4,694 individuals) were simply discarded and subsequently died. Moreover, our research noted that eight non-target species will become target species in the near future. Therefore, research on the reproductive biology of some marine crabs and an improved understanding of the importance of marine crabs by local fishermen are necessary to prevent biodiversity degradation and loss in this area.